The Mismatches Between Minority Language Practices and National Language Policy in Malaysia: A Linguistic Landscape Approach - Wang Xiaomei; Xu Daming (Kajian Malaysia, 2018)
The paper takes a linguistic landscape (LL) approach to the language use of two minority communities in Malaysia. A total of 689 digital photos of public signs were collected from two main streets in Chinatown and Little India, Kuala Lumpur and were analysed quantitatively with the aid of FileMaker 10.0. For each of the signs in the database, it is determined whether it is a monolingual or a multilingual sign, what language(s) is/are used in the sign, and which of the languages used is the dominant one in the case of a multilingual sign. On basis of the above characteristics of the signs, the visibility of the different languages in the linguistic landscape was analysed. The analysis shows the following ranking order of the visibility: Chinese, English and Malay in Chinatown; and English, Malay and Tamil in Little India. These findings show that the linguistic practices of the two ethnic minorities deviated from the language policy of the state, which is to promote Malay, the national language. The mismatches between the state policy and the minority community practice are explained both by the non-use value of identity expression and the use value of communication of LL and by the political and economic motivations of language policy.